Solution-printed organic semiconductor blends exhibiting transport properties on par with single crystals - Niazi, Muhammad R. (Nat Commun, 2015)
Solution-printed organic semiconductors have emerged in recent years as promising contenders for roll-to-roll manufacturing of electronic and optoelectronic circuits. The stringent performance requirements for organic thin-film transistors (OTFTs) in terms of carrier mobility, switching speed, turn-on voltage and uniformity over large areas require performance currently achieved by organic single-crystal devices, but these suffer from scale-up challenges. Here we present a new method based on blade coating of a blend of conjugated small molecules and amorphous insulating polymers to produce OTFTs with consistently excellent performance characteristics (carrier mobility as high as 6.7 cm(2) V(−1) s(−1), low threshold voltages of<1 V and low subthreshold swings <0.5 V dec(−1)). Our findings demonstrate that careful control over phase separation and crystallization can yield solution-printed polycrystalline organic semiconductor films with transport properties and other figures of merit on par with their single-crystal counterparts.